An integrative approach for codon repeats evolutionary analyses - Lousado, José Paulo (2012)
The relationship between genome characteristics and several human diseases has been a central research goal in genomics. Many studies have shown that specific gene patterns, such as amino acid repetitions, are associated with human diseases. However, several open questions still remain, such as, how these tandem repeats appeared in the evolutionary path or how they have evolved in orthologous genes of related organisms. In this paper, we present a computational solution that facilitates comparative studies of orthologous genes from various organisms. The application uses various web services to gather gene sequence information, local algorithms for tandem repeats identification and similarity measures for gene clustering.